The Study on Students’ Attitude Towards Physical Education Course - Xiang Yu, Wu; Yan, Chun (Lavai - International Journal of Education, 2022)
In today's world when physical education and health are becoming more important, the attitudes of non-physical education students towards this course rely on many factors. The purpose of this article is to reveal the attitudes of non-physical education students towards the Physical Education Course, and to clarify their causes and relationships. Questionnaire and interview methods were used in the research. Totally, 2232 students not majoring in Physical Education at the Hulunbuir University of The Inner Mongolia Autonomous Region, the People’s Republic of China participated in the questionnaire. A research methodology was developed to study students' attitudes towards Physical Education through a 27-question questionnaire and a 15-question interview. The questionnaire consisted of 4 sections: general information, attitude, participation and interest. In order to clarify the results of the questionnaire, interviews were conducted in each case. The developed questionnaire and interview were analyzed for the consistency and reliability and the obtained data underwent further qualitative and quantitively analyses. We came into conclusion that the attitudes towards the Physical Education Course by male students vary from those of the female students and the acknowledgement of the significance of the Course by students themselves increases their self-esteem, ability to work as a team, as well as learning efficiency.